Extraction of metal oxides from coal bottom ash by carbon reduction and chemical leaching - Itam Z.; Beddu S.; Mohammad D.; Kamal N.L.M.; Zainoodin M.M.; Syamsir A.; Razak N.A.; Hamid Z.A.A. (Elsevier Ltd, 2023)
Alumina; Aluminum oxide; Ash handling; Ashes; Carbon; Coal; Hematite; Leaching; Lime; Magnesia; Potassium compounds; Silica; Sodium compounds; Titanium dioxide; Waste disposal; Bottom ash; Carbon reduction; Chemical and physical properties; Chemical leaching; Coal bottom ash; Extraction and purifications; Extraction method; Metal-oxide; Phosphorous pentoxide; Waste products; Extraction